2013
DOI: 10.2166/wst.2013.369
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of C,N-codoped TiO2 photocatalyst for the degradation of diclofenac from wastewater

Abstract: Application of mesoporous C- and C,N-codoped TiO2 in the removal of diclofenac from water was studied. The sol-gel method was used for the preparation of the photocatalysts. The physicochemical properties of studied materials were characterized by BET (Brunauer, Emmett and Teller), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy and X-ray diffraction (XRD) methods. XPS confirmed the incorporation of nitrogen and carbon atoms into TiO2 lattice. The synthesized catalysts were effective in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…13–20%), containing N and/or C‐modified TiO 2 additives, is believed to be connected with the presence of the non‐metals in the TiO 2 structure. The higher photocatalytic activity of such modified photocatalysts was confirmed in the variety of photocatalytic oxidation processes [24–27] and ascribed to the formation of additional energy states in TiO 2 lattice. As presented in Table 2, the TiO 2 /N and TiO 2 /N,C photocatalysts displayed similar amounts of N, which might explain an almost identical NO (and NO x ) conversion on the Con + TiO 2 /N and Con + TiO 2 /N,C materials.…”
Section: Resultsmentioning
confidence: 99%
“…13–20%), containing N and/or C‐modified TiO 2 additives, is believed to be connected with the presence of the non‐metals in the TiO 2 structure. The higher photocatalytic activity of such modified photocatalysts was confirmed in the variety of photocatalytic oxidation processes [24–27] and ascribed to the formation of additional energy states in TiO 2 lattice. As presented in Table 2, the TiO 2 /N and TiO 2 /N,C photocatalysts displayed similar amounts of N, which might explain an almost identical NO (and NO x ) conversion on the Con + TiO 2 /N and Con + TiO 2 /N,C materials.…”
Section: Resultsmentioning
confidence: 99%
“…Co-doping may increase OHgroups on to the surface of nano-TiO 2 improving the stability of desired defects in TiO 2 crystal lattice and reducing the photo-generated electron hole pair recombinations [222,223]. For example, Buda and Czech et al (2013) achieved an effective (80%) degradation of diclofenac in wastewater by using carbon/nitrogen co-doped TiO 2 [224]. Segne et al (2011) [225] evaluated the photocatalytic degradation of pharmaceuticals using Mg +2 /Cu +2 co-doped TiO 2 which showed shifts in the absorbance band from UV to visible region reducing the band gap energy from 3.2 eV to 2.50 eV.…”
Section: Nano-tio 2 With Dopantsmentioning
confidence: 99%
“…Many publications have demonstrated that DCF can be decomposed due to the photocatalysis of TiO 2 [6][7][8][9][10]. Unfortunately, to our knowledge, only UV and near UV-Visible (366 nm) light were used to excite the photocatalytic decomposition of DCF so far [6][7][8][9][10], due to the restrictive light absorption of TiO 2 resulted from its wide band-gap [11]. From the viewpoint of utilizing solar light, visible light responsive TiO 2 photocatalysts with high activity for the decomposition of DCF are highly desired.…”
Section: Introductionmentioning
confidence: 99%